Response of Liquid Organic Fertilizer (LOF) from Tofu Wastewater and Lamtoro Leaves (Leucaena leucocephala) on the Growth of Red Spinach (Amaranthus tricolor L.) - Hidayah; Ambar Pratiwi; Eri Eryati (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Tofu wastewater contains total nitrogen (N), phosphorus (P), and potassium (K) at levels of 43.37 mg/L, 114.36 mg/L, and 223 mg/L, respectively. In addition, lamtoro leaves have potential as an organic fertilizer; every 100 g of fresh lamtoro leaves yields approximately 85% dry matter, containing 20–25% protein, 20–30% free nitrogen, 5–10% fat, 3.89% energy, 1.5–2.5% tannins, 0.8–1.8% calcium, and 0.23–0.27% phosphorus. These two materials can be processed into liquid organic fertilizer (LOF) and applied to red spinach cultivated in polybags. This study aimed to analyze C-NPK content, determine the optimal concentration of LOF to enhance red spinach growth, and identify the best growth parameters influenced by LOF application derived from tofu wastewater and lamtoro leaves. The independent variable was LOF concentration with four replications and five treatments: K (0%), A (5%), B (10%), C (15%), and D (20%). The dependent variables included plant height, number of leaves, leaf width, root length, root fresh weight, root dry weight, stem fresh weight, and stem dry weight. The results showed that the LOF contained 9.64% organic C, 0.57% N, 0.042% P, and 0.358% K. The optimal concentration was treatment C (15%). The best growth parameters were observed in root length, root fresh weight, stem fresh weight, and stem dry weight.